Der „Homo alpinus“. Eine kurze Notiz zu Willy Hellpachs Versuch, die Existenz von Bergmenschen auf ein umweltpsychologisches Fundament zu stellen - Patrick Stoffel (Góry, Literatura, Kultura)
In the first decades of the 20th century, Willy Hellpach attempted to explain the observation that mountain dwellers differ significantly from the inhabitants of the plains in terms of the influence of the natural environment on people’s mental life. Embedded in contemporary race theory, which he expanded to include elements of environmental psychology, he came to the conclusion that mountains, beyond the “racial origin” of their population, produce a soil phenotype due to the “abundance of things to cope with” that they offer in a very confined space: the Homo alpinus, being characterized by self-sufficiency and a rich imagination.